Changes in Physical Performance and Their Association With Health-Related Quality of Life in a Mixed Nonischemic Cardiac Population That Participates in Rehabilitation. Issue 2 (March 2020) - Tang, Lars Hermann; Zwisler, Ann-Dorthe; Doherty, Patrick; Oldridge, Neil; Berg, Selina Kikkenborg; Christensen, Jan
Abstract : Purpose: Exercise-based cardiac rehabilitation improves physical performance and health-related quality of life (HRQoL). However, whether improvements in physical performance are associated with changes in HRQoL has not been adequately investigated in a nonischemic cardiac population. Methods: Patients who were ablated for atrial fibrillation, who underwent heart valve surgery or who were treated for infective endocarditis, and who participated in 1 of 3 randomized controlled rehabilitation trials were eligible for the current study. Change in physical performance and HRQoL were measured before and after a 12-wk exercise intervention. Physical performance was assessed using a cardiopulmonary exercise test, a 6-min walk test, and a sit-to-stand test. Health-related quality of life was assessed using the generic 36-Item Short Form Health Survey and the disease-specific HeartQoL questionnaire. Spearman correlation coefficient (ρ) and linear regressions quantified the association between changes in physical outcome measures and changes in HRQoL. Results: A total of 344 patients were included (mean age: 60.8 ± 11.6 yr and 77% males). Associations between changes in physical outcome measures and HRQoL ranged from very weak to weak (ρ = −0.056 to 0.228). The observed associations were more dominant within physical dimensions of the HRQoL compared with mental or emotional dimensions. After adjusting for sex, age, and diagnosis, changes in physical performance explained no more than 20% of the variation in the HRQoL. Conclusion: The findings show that the positive improvement in HRQoL from exercise-based cardiac rehabilitation cannot simply be explained by an improvement in physical performance. Abstract : Whether improvements in physical performance are associated with changes in health-related quality of life has not been adequately investigated in a nonischemic cardiac population. Data obtained from 3 randomized controlled cardiac rehabilitation trials showed that changes in physical performance explained no more than 20% of the variation in the health-related quality of life.